Physiological Response and Endurance of Madurese Cattle and Their Crosses at The Tropical Environment in Pamekasan Regency - Agustina, Desi Kurniati; Hidayati, Nurul (Jurnal Agripet, 2025)
This study aimed to determine the physiological response of Madura cattle and Limura cattle (Limousin x Madura) to the tropical environment. The research was conducted in Galis District, Pamekasan Regency from July to August 2024. The sample consisted of 50 Madura and Limura cattle, selected by purposive sampling. The parameters observed included rectal temperature, respiratory frequency, heart rate frequency, Heat Tolerance Coefficient (HTC), as well as the microclimate of the pen, which included air temperature, relative humidity (RH), and Temperature Humidity Index (THI). The results showed that the average THI at the research site was 83.24. The average rectal temperature (C) in the morning, afternoon, and evening for Madura and Limura cattle were as follows: 37.71.5, 38.70.4, 37.20.7 for Madura cattle, and 38.60.5, 38.90.3, 38.50.3 for Limura cattle, respectively. The mean respiratory frequency (times/minute) in the morning, afternoon, and evening for Madura and Limura cattle were: 23.53.4, 28.66.8, 23.35.2 for Madura cattle, and 25.62.0, 30.32.0, 26.73.1 for Limura cattle, respectively. The mean heart rate (times/minute) in the morning, afternoon, and evening for both groups were similar: 65.34.2, 69.59.8, 65.16.7 for Madura cattle, and 65.43.8, 69.811.8, 66.54.2 for Limura cattle, respectively. The mean Heat Tolerance Coefficient (HTC) for Madura and Limura cattle were 2.10.23 and 2.20.1, respectively. It was concluded that both Madura and Limura cattle exhibit similar responses in terms of heart rate and respiration rate. However, Madura cattle have lower rectal temperatures than Limura cattle. The Heat Tolerance Coefficient (HTC) was found to be higher in Limura cattle compared to Madura cattle.